2022
DOI: 10.1111/azo.12452
|View full text |Cite
|
Sign up to set email alerts
|

Sex determination in domestic rock pigeons (Columba livia) using radiographic morphometry

Abstract: Determination of sex on the base of external morphological features is very difficult in most birds. However, molecular sex identification methods can be used for sexing of these so‐called monomorphic bird species. This study analysed the sexual dimorphism of radiographic morphometric features in rock pigeons whose sexes were determined by the molecular sex identification method. Body weights and 21 radiographic measurements of 43 rock pigeons (18 males and 25 females) were taken. Among cranium measurements, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Numerous studies have been conducted to investigate the anatomical, morphological and osteometric characteristics of the pelvis and other bony structures in the pelvic limb region of birds, specifically focusing on sexual dimorphism (Abdul‐Rahman et al., 2015; Frigot, 2019; Schnell et al., 1985; Silva et al., 2020; Szara et al., 2022). Furthermore, studies have reported that the majority of measurement parameters obtained from the pelvis tend to be higher in males compared to females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been conducted to investigate the anatomical, morphological and osteometric characteristics of the pelvis and other bony structures in the pelvic limb region of birds, specifically focusing on sexual dimorphism (Abdul‐Rahman et al., 2015; Frigot, 2019; Schnell et al., 1985; Silva et al., 2020; Szara et al., 2022). Furthermore, studies have reported that the majority of measurement parameters obtained from the pelvis tend to be higher in males compared to females.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely used in the diagnosis of many cases, such as hernia, tumours, ectopic eggs, fractures, lipoma, ovarian cystic hyperplasia, oophoritis and egg retention in pet birds (Durmus, 2022; Kılıcarslan, 2012; König et al., 2016; Krautwald‐Junghanns et al., 2011; Kubiak, 2020). Furthermore, this imaging method proves valuable in determining the sex of animals (Celimli et al., 2008; Leão et al., 2022; Monteiro et al., 2013; Pinheiro et al., 2016; Silva et al., 2020; Szara et al., 2022). To the best of our knowledge, there is currently no research available regarding the application of this method in determining the sex of budgerigars.…”
Section: Introductionmentioning
confidence: 99%
“…This difficulty is not just an inconvenience for researchers; it has significant implications for various aspects of avian biology, including understanding mating systems, population genetics, and conservation strategies. Accurate sex determination within a population allows researchers to investigate patterns of sex ratio, reproductive success, and gene flow, which are crucial for an effective understanding of evolutionary dynamics, conservation management, and added advantages in forensic cases [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies are focused on evolutionary and functional avian anatomy (Tokita et al, 2017;Marugán-Lobón and Buscalioni, 2006;Gussekloo et al, 2001). Additional studies are focused on the comparation and diversity (Pecsics, 2023;Zusi, 1993), or the detection of the sexual dimporphism, even if the birds do not show such clear sexual dimorphism as mammals (Szara et al, 2022a;Szara et al, 2022b;Pazvant et al, 2022;Gündemir et al, 2020a;Verdiglione and Rizzi, 2018;Rathert et al, 2017;Dillon, 2014).…”
Section: Introductionmentioning
confidence: 99%